PENGARUH DOSIS PUPUK NITROGEN DAN JUMLAH TANAMAN TERHADAP PERTUMBUHAN DAN HASIL CAISIM (Brassica sp) - Jati Purwani; Dwiwanti Sulistyowati (Jurnal Penyuluhan Pertanian, 2020)
Caisim (Brassica sp) is one of the most vegetables that grow well depending on climate and soil factors. Caisim planting in pots or polybags is an alternative way of vegetable planting in limited land. Fertilizing is an important factor in increasing caisim production, especially urea. On the other hand, to obtain the optimal caisim production in pots can be achieved by increasing the number of plants in pots. It is necessary to study the optimal number of plants per pot interaction with the provision of fertilizers (especially N). The pot experiment was done in a green house of University Farm, Institut Pertanian Bogor (IPB). The treatments consisted of 2 factors, the first factor was the levels of urea applications and the second factor was the number of plants per pot. Randomized Block Design was used with three replications. The results of the experiment show that maximum yield for the number of 1 plant/pot is 77,08 g/pot with 61,09 ppm urea. The maximum yield for 2 and 3 plants/pot were 185,26 g/pot and 221,23 g/pot with 143,11 and 163,76 ppm urea respectively. The results showed that the highest yield of caisim (Brassica sp) was obtained by the treatment of 3 plants/pot with 163 ppm urea.